SKRINING KADAR KOLESTEROL, ASAM URAT DAN GULA DARAH PADA KELOMPOK AISYIAH DENGAN FAKTOR RESIKO - Wibowo, Nugroho Ari; Priyantini, Diah; Wijaya, Siswanto Agung; Anandhita, Aries Chandra; Saputro, Suyatno Hadi; Rusdi, Ainur; Badriyah, Fatin Lailatul; Mukarromah, Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Health screening is present as a step that is not only important, but also very strategic in efforts to prevent and detect non-communicable diseases early. Not only that, this step can also contribute to reducing the burden of disease in society as a whole. By addressing health problems from an early stage, it is hoped that there will be a decrease in morbidity and mortality rates related to these diseases, as well as optimization of health resources in the community. Cholesterol, Uric Acid and Blood Sugar Level Screening Activities in the Aisyiah Group with Risk Factors Health screening activities were carried out on October 8, 2024 at One of the Aisyiah in Sidoarjo City. This activity was attended by 50 members of the Aisyiah Group who had risk factors for metabolic diseases. The purpose of the activity Routine health checks are very important for early detection of metabolic diseases such as diabetes, high cholesterol, and uric acid. The results of this community service show a fairly high prevalence of metabolic disorders in the Aisyiah Group who have these risk factors. These findings underscore the importance of special attention to metabolic health in this community. Metabolic disorders, such as type 2 diabetes and metabolic syndrome, can have serious long-term health impacts if not managed properly. This health screening activity successfully detected a number of Aisyiah Group members who had risk factors for metabolic diseases. This proves the importance of routine health checks as an effort for early detection and prevention of disease.